2014
DOI: 10.20491/isader.2014215951
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Burnout on Organizational Commitment in Logistics Sector

Abstract: Burnout is a psychological syndrome that reduces people's motivation, job satisfaction and organizational commitment. People whose jobs are related with human interaction are usually exposed to burnout. In the literature, three dimensions of burnout were defined as emotional exhaustion, depersonalization and reduced personal accomplishment. In this study antecedents (cynicism, role ambiguity, role conflict and organizational justice) and consequences (job satisfaction, organizational commitment) of burnout wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…According to the findings, affective commitment has a negative and significant effect on emotional exhaustion. This result is parallel to the research findings in the literature (Yener et al, 2014;Tosun & Ulusoy, 2017;Akpınar et al, 2013). Employees are less likely to feel their emotional resources in their work run out when they integrate with the organization and feel satisfaction with being a member of the organization.…”
Section: Discussion and Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…According to the findings, affective commitment has a negative and significant effect on emotional exhaustion. This result is parallel to the research findings in the literature (Yener et al, 2014;Tosun & Ulusoy, 2017;Akpınar et al, 2013). Employees are less likely to feel their emotional resources in their work run out when they integrate with the organization and feel satisfaction with being a member of the organization.…”
Section: Discussion and Resultssupporting
confidence: 89%
“…Researches in the literature have also provided findings in parallel with this expectation. For example, Yener et al (2014) found in the research they conducted with employees in a logistics sector that organizational commitment affected burnout negatively and significantly. Tosun and Ulusoy (2017) and Akpınar et al (2013) found as a result of a survey conducted by employees in the health sector that affective commitment negatively and significantly affects emotional exhaustion.…”
Section: H2:the Perception Of Job Insecurity Affects Employee's Emotimentioning
confidence: 99%
See 1 more Smart Citation
“…Specific to SCM, our study responds to a lack of empirical study of social support and employee retention to address the talent shortage (Hohenstein et al , 2014). As another contribution, our study shows that interference with family time (time-based WIF) does not diminish logistics job satisfaction, advancing findings on the impact of burnout in SCM (Yener, 2014). Finally, our study augments scarce research examining gender differences in SCM to support the gender imbalance, supporting concerns that WIF can be particularly problematic for women (Nix and Stiffler, 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Job demands refer to employees' challenging work conditions such as long working hours, poor working environment, high work pressure and emotionally demanding interactions. When employees try to meet these expectations, job demands may be stressful, resulting in physical or psychological damage (Bakker and Demerouti, 2017;Yener et al, 2014). It was claimed that job demands also result in workaholism, affecting employees negatively, such as reduced happiness and lower job satisfaction in the long term.…”
Section: Introductionmentioning
confidence: 99%